Niemcy w polityce globalnej (Biała Księga) - Miszczak, Krzysztof (Rocznik Polsko-Niemiecki, 2017)
The aim of this article is to analyse the global and European foreign, security and defence policies of the Federal Republic of Germany and their implications for the broad international environment of Germany. Special attention is paid to the issues of Germany’s emancipation in the international order after the end of the East-West conflict, when it became clear that the regional conflicts and their transnational impact gained a new and multidimensional character for the German security policy. Given this evolution of the international system, Germany has gradually changed its former foreign and security policies. The state currently intends to take greater responsibility for international politics, which translates into a simultaneous increase in its political and economic power in the international arena. This new global role of the Federal Republic of Germany is manifested by the so-called White Paper on German Security Policy and the Future of the Bundeswehr approved on 13 July 2016. This document presents primarily the hierarchy of threats in today’s world, their definitions and attempts to neutralize them in compliance with German interests. Instruments to ensure a smooth achievement of this goal include the modernization of the German armed forces, the creation of intervention troops and their participation in multinational military operations conducted by NATO and the European Union.